Craniospinal irradiation using helical tomotherapy for central nervous system tumors. (17th January 2017) - Schiopu, Sanziana R.I.; Habl, Gregor; Häfner, Matthias; Katayama, Sonja; Herfarth, Klaus; Debus, Juergen; Sterzing, Florian
Abstract: The aim of this study was to describe early and late toxicity, survival and local control in 45 patients with primary brain tumors treated with helical tomotherapy craniospinal irradiation (HT-CSI). From 2006 to 2014, 45 patients with central nervous system malignancies were treated with HT-CSI. The most common tumors were medulloblastoma in 20 patients, ependymoma in 10 patients, intracranial germinoma (ICG) in 7 patients, and primitive neuroectodermal tumor in 4 patients. Hematological toxicity during treatment included leukopenia Grades 1–4 (6.7%, 33.3%, 37.8% and 17.8%, respectively), anemia Grades 1–4 (44.4%, 22.2%, 22.2% and 0%, respectively) and thrombocytopenia Grades 1–4 (51.1%, 15.6%, 15.6% and 6.7%, respectively). The most common acute toxicities were nausea, vomiting, fatigue, loss of appetite, alopecia and neurotoxicity. No Grade 3 or higher late toxicity occurred. The overall 3- and 5-year survival rates were 80% and 70%, respectively. Survival for the main tumor entities included 3- and 5-year survival rates of 80% and 70%, respectively, for patients with medulloblastoma, 70% for both in patients with ependymoma, and 100% for both in patients with ICG. Relapse occurred in 11 patients (24.4%): 10 with local and 1 with multifocal relapse. One patient experienced a secondary cancer. M-status and the results of the re-evaluation at the end of treatment were significantly related to survival. Survival after HT-CSI was in line with the existing literature, and acute treatment-induced toxicity resolved quickly. Compared with conventional radiotherapy, HT offers benefits such as avoiding gaps and junctions, sparing organs, and better and more homogeneous dose distribution and coverage of the target volume.